The shale gas revolution in China—problems and countermeasures - Xiaohui Chen; Zhicheng Liu; Xin Liang; Zhao Zhang; Tingshan Zhan; Haihua Zhu; Jun Lang (Earth Sciences Research Journal)
Shale gas development throughout the world has resulted in a revolution in the field of global energy and has also become an important topic in China in recent years. While organic-rich shale is widely distributed in China and the initial commercialization of shale gas has been achieved, the research, exploration, and development of shale gas remain at an early stage. Problems exist with crucial technologies, innovation, institutional mechanisms, environmental protection, and other aspects of the industry. The shale gas exploration and development industry in China can learn from the experiences of other countries and strengthen its position in the market, with the support of new government policy. Given its unique geological conditions, China should speed up the introduction of technical innovation and establish its unique systems and methods for shale gas exploration and development.